Fator erosividade da chuva de Piraju (SP): distribuição, probabilidade de ocorrência, período de retorno e correlação com o coeficiente de chuva - Roque, C. G. [UNESP]; Carvalho, M. P. [UNESP]; Prado, R. M. [UNESP] (Sociedade Brasileira de Ciência do Solo, 2001)
A set of 874 erosive individual rainfall occurrences was selected from a continuous serie of twenty-three years of recording rain gauge data. All the selected rainfall occurrences were analized. The rainfall erosivity factor computed was 7074 MJ mm ha-1 h-1 y-1, which is expected to occur at least once every 2.33 years, with a probability of occurrence of 42.92%. The values of the annual erosivity indexes at that site expected for the return periods of 2, 5, 10, 20, 50, and 100 years, were respectively 6,696, 8,730, 10,076, 11,367, 13,039, and 14,292 MJ mm ha-1 h-1 y-1. The most annual soil loss is expected to ocour between the months of October and March (78.5%) where 46.9% occurs between december and february of the total annual erosivity for that period, in whose periods is expected high erosion soil loss. A high correlation was found between the montly average erosivity index EI30 and the rainfall coefficient at that site. Therefore, the regression equation obtained allows a fair estimative of the R factor to be used for other regions where climatic conditions are similar to Piraju's and where there are no available data.

Foram selecionadas 874 chuvas individuais erosivas, de uma série contínua de 23 anos de registros de dados pluviográficos. As chuvas selecionadas foram cotadas, digitalizadas e, posteriormente, analisadas. O índice de erosividade, EI30, médio anual calculado foi de 7.074 MJ mm ha-1 h-1 ano-1. Espera-se que este índice ocorra no local pelo menos uma vez a cada 2,33 anos, com uma probabilidade de 42,92%. Os valores dos índices anuais de erosividade de Piraju, esperados nos períodos de retorno de 2, 5, 10, 20, 50 e 100 anos, foram, respectivamente, de 6.696, 8.730, 10.076, 11.367, 13.039 e 14.292 MJ mm ha-1 h-1 ano-1. Foi observada uma distribuição de 78,5% do total da erosividade anual durante o semestre de outubro a março, indicando que, nesse período, era esperada a maior parte das perdas de solo por erosão. Observou-se elevada correlação entre o índice de erosividade, EI30, médio mensal e o coeficiente de chuva. Portanto, a equação de regressão determinada permite que seja estimado, com boa margem de segurança, o EI30 para outros locais que não possuam dados pluviográficos, mas que disponham de dados pluviométricos e condições climáticas semelhantes às de Piraju (SP).
Rainfall erosivity factor at Piraju (SP), Brazil: distribution, probability of occurrence, return period and correlation with rainfall coefficient
Keywords: fator R; erosão do solo; equação universal de perda de solo; erosividade; R factor; soil erosion; universal soil loss equation; erosivity